Numerical Simulation of Impingement Heat Transfer for a Laminar Premixed Bunsen Flame - Darya A. Slastnaya; Roman V. Tolstoguzov; Leonid M. Chikishev; Vladimir M. Dulin (Energies)
Flame impingement heat transfer is implemented in many industrial applications. The laminar premixed Bunsen flame, impinging on a flat cold surface, represents a basic model for the validation of computational fluid dynamics (CFD) codes, used for the simulation of industrial processes. Meanwhile, as the present paper demonstrates, some features of basic flame configurations are not well-reviewed. The present paper reports on the direct numerical simulation of the thermofluidic field in a laminar premixed impinging Bunsen flame in comparison with advanced optical measurements. The results reveal the phenomenon of the central recirculation zone formation between the tip of the Bunsen flame cone and the cold surface. Cooled combustion products concentrate inside this zone, resulting in reduced heat transfer near the flow axis. All three tested chemical kinetic mechanisms (GRI-Mech 3.0, SanDiego, RMech1) provide reasonable predictions of the observed phenomenon, which explain previous experimental observations on the reduced heat transfer at the central axis of impinging flames. Moreover, the most detailed mechanism, GRI-Mech 3.0, predicts an elevated concentration of NOX pollutants caused by the mentioned phenomenon.